Особливості стану тканин пародонта в дітей-інвалідів із хворобами центральної нервової системи - Гавриленко, М. А.; Gavrilenko, M. A. (УМСА, 2015)
Наведені результати обстеження стану тканин пародонта в 98 дітей- інвалідів віком від 2 до 18 років із хворобами центральної нервової системи. Виявлено високу поширеність та інтенсивність захворювань тканин пародонта. Приведены результаты обследования состояния тканей пародонта у 98 детей-инвалидов в возрасте от 2 до 18 лет с заболеваниями центральной нервной системы. Выявлена высокая распространенность и интенсивность заболеваний тканей пародонта. The article presents the results of investigation of condition of periodontal tissues in 98 children with disabilities aged from 2 to 18 years with diseases of the Central nervous system. High prevalence and intensity of diseases of fabrics of parodont. It is known that the leading cause of periodontal diseases is poor oral hygiene. Periodontal diseases remain among the most common dental diseases. There are a number of modern publications on the treatment of inflammatory and destructive periodontal diseases. But its implementation is impossible in such a category of patients as disabled children with diseases of the central nervous system. Therefore, an important task is the timely prevention of dental diseases in these children.
Features of condition of periodontal tissues in disabled children with central nervous system diseases
Keywords: діти-інваліди з хворобами центральної нервової системи; гінгівіт; пародонтит; дети-инвалиды с заболеваниями центральной нервной системы; гингивит; disabled children with diseases of the Central nervous system complicated caries; low level of oral hygiene